2015
DOI: 10.4414/smw.2015.14102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of local vascular lesions assessed with optical coherence tomography and ablation points on blood pressure reduction after renal denervation

Abstract: Our study demonstrates for the first time that the number and type of vascular lesions as assessed with OCT did not predict the success of BP reduction after RDN. However, we observed a substantial decrease in office SBP in relation to the number of ablation points at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Nevertheless, the problems associated with this procedure should not be ignored. Currently, although the number of patients who undergo percutaneous endovascular RDN is limited and the follow-up period is short, some side effects have been reported [15], i.e., lumen stenosis, atrial wall hematoma, intimal tears, intraluminal thrombosis, intima-media thickening [16][17][18][19], etc. Most of these factors may be caused by the direct delivery of RF energy or stimulation of the endothelium by the wire and catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the problems associated with this procedure should not be ignored. Currently, although the number of patients who undergo percutaneous endovascular RDN is limited and the follow-up period is short, some side effects have been reported [15], i.e., lumen stenosis, atrial wall hematoma, intimal tears, intraluminal thrombosis, intima-media thickening [16][17][18][19], etc. Most of these factors may be caused by the direct delivery of RF energy or stimulation of the endothelium by the wire and catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Ablation Sites. As is reported in previous studies, the number of ablation sites in each renal artery has been considered as a major influence factor for prediction of office SBP [24,64], rather than 24 h-ABPM [13,64,65] after RDN. Furthermore, ablations at different segments of renal artery are also confounding factors affecting the outcome of RDN.…”
Section: Procedural Factorsmentioning
confidence: 94%
“…This study also confirmed that short-and long-term side effects of sympathetic renal denervation are minimal. 37,45,58,59 The important insights provided by the Symplicity HTN3 and DENERHTN studies J U…”
Section: Catheter-based Renal Nerve Denervationmentioning
confidence: 99%